Sustainable Solution for Plastic Pollution: Upcycling Waste Polypropylene Masks for Effective Oil-Spill Management - Junaid Saleem (14670322) (2023)
The use of Polypropylene PP in disposable items such as face masks, gloves, and personal protective equipment has increased exponentially during and after the COVID-19 pandemic, contributing significantly to microplastics and nanoplastics in the environment. Upcycling of waste PP provides a useful alternative to traditional thermal and mechanical recycling techniques. It transforms waste PP into useful products, minimizing its impact on the environment. Herein, we synthesized an oil-sorbent pouch using waste PP, which comprises superposed microporous and fibrous thin films of PP using spin coating. The pouch exhibited super-fast uptake kinetics and reached its saturation in fewer than five minutes with a high oil uptake value of 85 g/g. Moreover, it displayed high reusability and was found to be effective in absorbing oil up to seven times when mechanically squeezed between each cycle, demonstrating robust oil-sorption capabilities. This approach offers a potential solution for managing plastic waste while promoting a circular economy. Other Information Published in: International Journal of Molecular Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijms241512368